1991
DOI: 10.1063/1.347445
|View full text |Cite
|
Sign up to set email alerts
|

The growth kinetics of diamond films deposited by hot-filament chemical vapor deposition

Abstract: Articles you may be interested inCompositional mapping of the argon-methane-hydrogen system for polycrystalline to nanocrystalline diamond film growth in a hot-filament chemical vapor deposition system Silver on diamond Schottky diodes formed on boron doped hotfilament chemical vapor deposited polycrystalline diamond filmsThe morphology changes in diamond synthesized by hotfilament chemical vapor depositionThe growth kinetics of diamond film has been studied, grown by a hot-filament chemical vapor deposition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, despite the commercial importance of high growth rates and the potential for gaining insight into the details of the growth mechanism, only a handful of studies of the growth kinetics of polycrystalline diamond films have been reported. [5][6][7][8][9] There is a clear but unmet need for systematic studies of CVD growth kinetics on individual crystal faces of diamond. Interpretation of the growth kinetics of polycrystalline films is complicated greatly by the presence of both (100) and (111) crystal faces under typical growth conditions, whose relative areas depend on both the substrate temperature and the composition of the gas phase.…”
Section: Fia-jmentioning
confidence: 99%
“…However, despite the commercial importance of high growth rates and the potential for gaining insight into the details of the growth mechanism, only a handful of studies of the growth kinetics of polycrystalline diamond films have been reported. [5][6][7][8][9] There is a clear but unmet need for systematic studies of CVD growth kinetics on individual crystal faces of diamond. Interpretation of the growth kinetics of polycrystalline films is complicated greatly by the presence of both (100) and (111) crystal faces under typical growth conditions, whose relative areas depend on both the substrate temperature and the composition of the gas phase.…”
Section: Fia-jmentioning
confidence: 99%
“…In diamond CVD reactors, researchers found that hydrogen atom production decreases with increased methane concentration. [47][48][49][50] In our case, atomic hydrogen etching and cutting effects are found to be very sensitive to the ow rate of CH 4 . Fig.…”
Section: Resultsmentioning
confidence: 51%
“…During HFCVD process, various gas phase radicals are produced on and near the hot filament and the chemistry of these radicals on the substrate plays an important role in the growth of diamond film [5,6]. Conventionally, HFCVD grown microcrystalline diamond (MCD) films exhibit a faceted morphology with large surface roughness when it is grown with low CH4 to H2 ratio.…”
Section: Introductionmentioning
confidence: 99%